Molecular dynamics simulations of nanoindentation and scratch in Cu grain boundaries - Liang, Shih-Wei; Qiu, Ren-Zheng; Fang, Te-Hua (Beilstein Journal of Nanotechnology, 2017)
The dynamic nanomechanical characteristics of Cu films with different grain boundaries under nanoindentation and scratch conditions were studied by molecular dynamics (MD) simulations. The type of grain boundary is the main factor in the control of the substrate atoms with respect to the size of dislocations since the existence of the grain boundary itself restricts the movement associated with dislocations. In this work, we analyzed the transverse and vertical grain boundaries for different angles. From the simulation results, it was found that the sample with a transverse grain boundary angle of 20° had a higher barrier effect on the slip band as compared to samples with other angles. Moreover, the nanoindentation results (i.e., indentation on the upper area) of the vertical grain boundary showed that the force was translated along the grain boundary, thereby producing intergranular fractures.
Keywords: indentation; molecular dynamics; nanograin boundary; nanoscratch